Cardiac stimulant activity of bark and wood of Premna serratifolia - Saleem Basha N; Rekha Rajendran; Meenakshi Sundaram R; Suseela L (Bangladesh Pharmacological Society, 2008)
Premna serratifolia Lin., (Verbenaceae) contains alkaloids and iridoid glycoside and is believed to prevent cardiovascular disease. The stem-bark and stem-wood were extracted with 95% ethanol and distilled water. These extracts were screened for their effects by Isolated Frog Heart Perfusion Technique and biochemical parameters in heart tissue and serum of albino rats after administering the extracts for 7 days. The ethanol extract produced significant positive ionotropic and negative chronotropic actions similar to that of digoxin on frog heart and its effect was inhibited by nifedipine and not by propranolol. A significant decrease in membrane Na+K+ATPase and Mg2+ATPase and an increase in Ca2+ATPase further confirmed its cardiotonic activity. Aqueous extract produced positive ionotropic and chronotropic effects similar to that of Adrenaline and its effect was antagonized by propranolol and nifedipine. The results suggest that the ethanol extract produced cardiotonic effect and the aqueous extract produced β-adrenergic effect.